Effect of small amount of alumina on structure, wear and mechanical properties of 3Y-TZP ceramics. (1st March 2014) - Danilenko, Igor; Prokhorenko, Serhii; Konstantinova, Tetyana; Ahkozov, Leonid; Burkhovetski, Valerii; Glazunova, Valentina
Abstract : The use of ceramic instead of metallic parts in devices that operate in aggressive conditions increases the service life of machines and equipment for chemical, metallurgical and other industries. The wear resistant zirconia/alumina composites were sintered from nanopowders obtained by co-precipitation technique. In the case of addition of 1wt% of alumina in zirconia ceramics the wear resistance increased by approximately 30%. The formation of complex multilevel composite structures, such as Al 3+ ion segregation on zirconia grain boundaries and intracrystalline alumina inclusions in zirconia grains, increased the fracture toughness values of composites obtained from co-precipitated nanopowders and consequently decreased the volume loss of ceramic material. In this study, we investigated the effect of nanopowders synthesis methods and alumina concentration on composite structure, fracture toughness and tribological behavior of 3Y-TZP/alumina ceramic composites and searched correlation between structures and mechanical properties.